IMPLEMENTASI METODE UCD (USER CENTERED DESIGN) DALAM RANCANG BANGUN GAME EDUKASI ANAK USIA DINI BERBASIS ANDROID: IMPLEMENTASI METODE UCD (USER CENTERED DESIGN) DALAM RANCANG BANGUN GAME EDUKASI ANAK USIA DINI BERBASIS ANDROID - Khana Wijaya (LPPM Universitas Abdurrab, 2023)
Over time, technological advances have developed very rapidly and have had a considerable impact in various fields, one of which is in the field of education. Education is a learning process that is obtained by every human being, in this case students, the goal is to make students understand, understand and be able to think more critically. Education can be formulated as a guide for human growth from birth to physical and spiritual maturity, in the interaction of nature and the social environment. Education is a continuous process, not stopping. Education is the most important thing in our lives, because with education humans can be helped in surviving and solving a problem. And being an educated person is very important. The first education we get is from the family environment, school environment, and community environment. Early age is a golden age for children to accept and grasp new things. The method used by researchers in this research is descriptive with a qualitative approach. The purpose of this research is to build an educational game application that can be implemented by early childhood. The design and development of this application helps children aged 3-5 years to better understand material about recognizing letters, numbers, fruit, animal colors, shapes and vehicles. as well as optimizing the functions of android devices owned by parents to serve as educational tools for their children.